Perspectives on a virtual student-led research conference in ophthalmology - Pur, Daiana R; Samuel, Andrew; Sothivannan, Amirthan; Tanya, Stuti M; Nguyen, Anne X (Canadian Medical Education Journal, 2023)
Implication Statement We share our experience of organizing a one-day virtual educational event, the first Canadian national student ophthalmology conference, in response to the need for ophthalmology career exploration. The conference included mentorship with residents, research presentations, keynote speakers, and more. Following the event, students expressed some improvement in accessing ophthalmology mentorship and research opportunities, along with a modest enhancement in their understanding of the specialty. We provide insights into the organizational framework and quality improvement results, aiming to assist students in adapting similar events for various specialities.